Ability to acquire resistance to trypanosome infections and growth of N'Dama cattle - Wissocq, N.M.; D'Ieteren, G.D.M.; Trail, J.C.M.; Monsengo, B. (OAU/STRC, 1999)
Earlier research had provided clear indications of an ability of N'Dama cattle to acquire, over time, some control of the Development of parasitaemia following a T. vivax infection but not apparently, following a T. congolense infection. The objective of this study is to further assess the importance of the ability to acquire resistance to trypanosome infection and its possible linkage with anaemia control and growth of trypanotolerant N'Dama cattle.